Review of medical physiology - Ganong, William F (Lange Medical Books, 2001)
* The bestselling and most current medical physiology book revised every other year * Review section reflects current USMLE United States, Medical Licensing Examinations standards * Market: Medical Students, Physical Therapy, Physician Assistant, Nursing and other health-related professions
Lange medical book
Keywords: biologie; Physiology; biologické vědy; fyziologie; Biological Science Disciplines